Impact of a Hospital Evidence‐Based Practice Center (EPC) on Nursing Policy and Practice. Issue 1 (3rd February 2019) - Lavenberg, Julia G.; Cacchione, Pamela Z.; Jayakumar, Kishore L.; Leas, Brian F.; Mitchell, Matthew D.; Mull, Nikhil K.; Umscheid, Craig A.
Abstract: Background: In 2006, our healthcare system created a hospital Evidence‐based Practice Center (EPC) to support the local delivery of high‐quality, safe and high value patient care. Since then, the importance of healthcare staff work life has also been highlighted, and together these four elements form the Quadruple Aim framework. Synergistic to this Aim, the Magnet ® program promotes and recognizes organizational nursing excellence. Objective: To examine the EPC's work to inform nursing policy and practice in support of the goals of the Quadruple Aim framework and Magnet ® designation. Methods: Methods used included the following: (1) descriptive analysis of the hospital EPC's database of rapid reviews; and (2) administration of a 40‐item electronic questionnaire to nurses who requested an EPC review during fiscal years (FY) 2015 and 2016. Results: Of 308 rapid reviews completed in the EPC's first 10 years, 59 (19%) addressed nursing topics. The proportion of reviews relevant to nursing increased from 5% (2/39) in the center's first 2 years to 44% (25/60) in FY 2015–2016. The majority of nursing reviews (39/59) examined processes of care. Of 23 nurses eligible to participate in the survey, 21 responded (91%). Nurses with administrative or managerial responsibilities requested 70% of reviews; clinical nurse specialists and bedside nurses requested 17% and 9%, respectively. Reviews were used to support clinical program development (48%), provide clinical guidance (33%), update nursing policies or procedures (24%) and develop training and curricula (24%). Nurses were satisfied with the hospital EPC reviews (mean; 4.7/5), and 95% indicated they were likely to request a future review. Linking Evidence to Action: A dedicated hospital EPC in partnership with nursing offers a unique mechanism for promoting a culture of evidence‐based practice. Nurses at all organizational levels use the services of a hospital EPC to inform nursing policy and practice and are highly satisfied with the process, supporting the Quadruple Aim and Magnet ® designation.